2021
DOI: 10.3390/nu13103452
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol’s Impact on the Fetus

Abstract: Background: Alcohol is a teratogen and prenatal exposure may adversely impact the developing fetus, increasing risk for negative outcomes, including Fetal Alcohol Spectrum Disorder (FASD). Global trends of increasing alcohol use among women of childbearing age due to economic development, changing gender roles, increased availability of alcohol, peer pressure and social acceptability of women’s alcohol use may put an increasing number of pregnancies at risk for prenatal alcohol exposure (PAE). This risk has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 118 publications
(154 reference statements)
0
24
0
6
Order By: Relevance
“…It is now recognized that fetal alcohol exposure during any gestation period can have serious teratogenic effects on embryo development and lead to FASD, [1][2][3][4][5]14 yet the impact of alcohol exposure during the preimplantation period, a particularly vulnerable developmental window, 83 remains considerably understudied. Although FASD is a worldwide public health burden, 12,131 there are no tangible measures to proactively mitigate the effects of fetal alcohol exposure prior to birth.…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that fetal alcohol exposure during any gestation period can have serious teratogenic effects on embryo development and lead to FASD, [1][2][3][4][5]14 yet the impact of alcohol exposure during the preimplantation period, a particularly vulnerable developmental window, 83 remains considerably understudied. Although FASD is a worldwide public health burden, 12,131 there are no tangible measures to proactively mitigate the effects of fetal alcohol exposure prior to birth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is estimated that the prevalence of alcohol use during pregnancy in the world population is 9.8% [ 10 ]. When consumed by pregnant women, alcohol is particularly harmful to the developing fetus [ 11 , 12 ]. Prenatal exposure to alcohol (PAE) is a challenging public health problem, and alcohol can induce, in the fetus, severe physical and mental impairments described as fetal alcohol syndrome (FAS) [ 13 ] or fetal alcohol spectrum disorders (FASD) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in adult mammals, PAE affects hippocampal neurogenesis [ 19 ]. PAE also severely affects the heart, leading to congenital cardiac diseases [ 20 ] These dysfunctions mostly result in miscarriage or are detected at birth in survival children [ 12 ]. However, the effects of ethanol on the heart of adults with PAE are little explored.…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of birth defects are caused by simple chromosomal aberrations or gene mutations, and the remaining about 80% are caused by environmental factors or the gene–environment interaction [ 8 ]. Previous epidemiological studies have shown that mothers with lower socioeconomic status, drinking, tobacco exposure, occupational exposure, air-pollution exposure, and gestational diabetes mellitus were related to the increased risk of birth defects [ 9 , 10 , 11 , 12 , 13 , 14 ]. Therefore, an in-depth investigation of the potential causes of birth defects, especially environmental risk-exposure factors that could require intervention, is a key step for prenatal education and primary prevention.…”
Section: Introductionmentioning
confidence: 99%